Shared Power, Responsibility, and Trust in Collaborative Management in the Institutional Team for Accelerating Stunting Reduction in Southwest Papua Province - Kadar, Anhar Akib; Ibrahim, Muhammad Akmal; Musa'ad, Muhammad (KnE Social Sciences, 2025)
Stunting is a complex problem that requires government intervention based on collaboration. This collaborative approach in practice is through the Stunting Reduction Acceleration Team (TPPS). Encouraging an effective collaboration process requires shared power, responsibility, and trust between collaborating actors. Therefore, this study aims to analyze shared power, responsibility, and trust in collaboration management in the Stunting Reduction Acceleration Team (TPPS) institution in West Papua Province. This study uses a qualitative approach. The informants interviewed were actors or regional apparatus organizations involved as institutional members of the Stunting Reduction Acceleration Team in Southwest Papua Province. Data collection was carried out through observation, in-depth interviews, and documentation studies. Data analysis consists of data collection, data reduction, data presentation, and drawing conclusions. The results of the study found that stunting reduction through TPPS institutions was less effective due to sectoral egos. Shared power is not evenly distributed, especially for policies and budgets. The greatest responsibility is held by the regional apparatus organizations that are the leading sectors in stunting reduction compared to other members of the TPPS. All members of the Stunting Reduction Acceleration Team (TPPS) build trust with each other in the collaboration process.